Frequency of Complications by Serum Sodium Level Among Patients with Liver Cirrhosis - Shaharyar Hussain, Muhammad Yaseen, Komal Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim of current study is to determine the prevalence of complication among patients with liver cirrhosis by serum sodium level. Study Design: Case-Control study Place and Duration: DHQ Hospital Faisalabad.June 2020-Dec 2020 Methods: There were one hundred and sixty patients of both sexes had liver disease cirrhosis with ages 18-75 were included. Age, gender, height and weight, BMI, and other medical conditions were collected after informed written permission was obtained from each participant. The blood sodium levels and severity of problems of 160 inpatients were evaluated. Child Pugh class was implemented. SPSS 24.0 version was used to analyze complete date. Results: In our study most of the cases 102 (63.8%) were males and 58 (36.2%) females. Age of the patients was 53.6±11.28 years and mean BMI was 25.4±8.31 kg/m2.HBV was the most common cause of liver disease found in 95 (59.8%) cases followed alcohol in 40 (25%) cases. Mean MELD score was 13.9±6.44. Most of the cases had child-pugh class C 80 (50%). We found that majority of the cases 79 (49.4%) had serum sodium level (>135meq/l) followed by hyponatraemia (<130meq/l)) in 42 (26.3%) and 39 (24.4%) patients had serum sodium level (131-135meq/l). We found ascites was the most common complication found in 132 (82.5%) patients with, followed by esophageal varix and hepatic encephalopathy. Severity of complications was significantly found in cases of hyponatraemia. Conclusion: As a result, we came to the conclusion that hyponatremia, particularly serum levels less than 130 mmol/L, might suggest the presence of serious problems associated with liver cirrhosis.